The Generation of Two Induced Pluripotent Cell Lines from Patients with an Atypical Familial Form of Lung Fibrosis - Eid Al-Mutairy; Somaya M. Al Qattan; Faiqa Imtiaz; Azizah AlAnazi; Angela Inglis; Rana Al-Rabiah; Reem S. Al-Hejailan (Cells)
Background: Pulmonary fibrosis is a major disease that leads to the progressive loss of lung function. The disease manifests early, resulting in type 2 respiratory failure. This is likely due to the bronchocentric fibrosis around the major airways, which causes airflow limitation. It affects approximately three million patients worldwide and has a poor prognosis. Skin fibroblasts isolated from patients offer valuable insights into understanding the disease mechanisms, identifying the genetic causes, and developing personalized therapies. However, the use of skin fibroblasts to study a disease that exclusively impacts the lungs is often questioned, particularly since lung fibrosis primarily affects the alveolar epithelium. Method: We report the reprogramming of skin fibroblasts from patients with an atypical early-onset form of lung fibrosis into induced pluripotent stem cells (iPSCs) and subsequently into alveolar epithelial cells. This was achieved using a Sendai virus approach. Results: We show that the reprogrammed cells carry mutations in the calcium-binding protein genes S100A3 and S100A13, leading to diminished protein expression, thus mimicking the patients’ cells. Additionally, we demonstrate that the generated patient iPSCs exhibit aberrant calcium and mitochondrial functions. Conclusions: Due to the lack of a suitable animal model that accurately resembles the human disease, generating patient lung cells from these iPSCs can provide a valuable “disease in a dish” model for studying the atypical form of inherited lung fibrosis. This condition is associated with mutations in the calcium-binding protein genes S100A3 (NM_002960) and S100A13 (NM_001024210), aiding in the understanding of its pathogenesis.